THE RELATIONSHIP BETWEEN POST-OF-MOTHERS' KNOWLEDGE ABOUT UMBILICAL CORD CARE AND THE DURATION OF UMBILICAL CORD REMOVAL - Ichtiar Agusria Gulo; Indah Putri Amanda; Lestari Gulo; Gracea Love Tamaro Sitorus; Elv. Feedia Mona Saragih (PT. Radja Intercontinental Publishing, 2025)
Background:The postpartum period is a crucial phase for both mother and baby, especially regarding umbilical cord care. Umbilical cord infections can cause severe complications and even death. At PMB Elly, many postpartum mothers still lack sufficient knowledge, which affects the time taken for the umbilical cord to fall off Objective: This study was designed to assess the relationship between the level of postpartum mothers' knowledge about umbilical cord care and the duration of umbilical cord detachment at PMB Elly in 2025. Methods: This study utilized a quantitative descriptive design involving a population of 30 postpartum mothers at PMB Elly. The total sampling technique was applied to select participants. Primary Data collection involved questionnaires, followed by univariate and bivariate analysis via the Chi-Square test. .Results: the bivariate analysis yielded a p-value of 0.000, demonstrating a significant correlation between maternal knowledge and the duration of umbilical cord separation. Conclusion: Good knowledge among postpartum mothers contributes to faster umbilical cord detachment.